2022
DOI: 10.1021/acs.chemrestox.1c00274
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Heterocyclic Aromatic Amines in Neurodegeneration

Abstract: Heterocyclic aromatic amines (HAAs) are mainly formed in the pyrolysis process during high-temperature cooking of meat. Meat consumption is very typical of the western diet, and the amount of meat consumption in the eastern countries is growing rapidly; HAAs represents widespread exposure. HAAs are classified as possible human carcinogens; numerous epidemiological studies have demonstrated regular consumption of meat with HAAs as risk factor for cancers. Specific HAAs have received major attention. For example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 145 publications
0
10
0
Order By: Relevance
“…HAAs are produced in meat upon high temperature cooking, through Maillard reaction between amino acids, sugar, and creatinine or pyrolysis of aromatic amino acids (11,12). HAAs have been classified into different subclasses, α-carbolines, aminoimidazoaazarenes (AIAs), and β-carbolines (9). Amongst AIA HAAs 2-Amino-1methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) is the most abundant and extensively studied HAA (13), where levels in chicken may reach 480 ng/g and human exposures of 0.5 -1 µg/day (though exposures could be as high as 5-50 µg) (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAAs are produced in meat upon high temperature cooking, through Maillard reaction between amino acids, sugar, and creatinine or pyrolysis of aromatic amino acids (11,12). HAAs have been classified into different subclasses, α-carbolines, aminoimidazoaazarenes (AIAs), and β-carbolines (9). Amongst AIA HAAs 2-Amino-1methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) is the most abundant and extensively studied HAA (13), where levels in chicken may reach 480 ng/g and human exposures of 0.5 -1 µg/day (though exposures could be as high as 5-50 µg) (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…The study of dietary neurotoxicants is important to a) determine the underlying pathogenic mechanisms that may influence neurodegeneration and b) identify modifiable risk factors that can limit the onset or progression of disease pathology. Previous studies have identified significant neurotoxic effects of dietary toxicants such as heterocyclic aromatic amines (HAA) on dopaminergic and cholinergic neurons, linking their potential association with AD and PD (5)(6)(7)(8)(9)(10). HAAs are produced in meat upon high temperature cooking, through Maillard reaction between amino acids, sugar, and creatinine or pyrolysis of aromatic amino acids (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Several of these chemicals have been linked to neurodegeneration. For instance, heterocyclic aromatic amines formed during high-temperature cooking of meats, including PhIP, have been linked to Parkinson’s and Alzheimer’s diseases ( Syeda and Cannon, 2022 ). Exposure to cupric oxide promoted neurotoxicity and neurodegeneration in a Caenorhabditis elegans model ( Mashock et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heterocyclic aromatic amines are a class of polycyclic aromatic compounds that are formed naturally during the heating of protein-based foods such as meat (19). The average exposure to meat HAAs varies by the nation due to differences in the diets of the East and West, especially the amount of meat consumed (20). Studies have shown that the average daily exposure to HAAs is 565.3 ng/d in Americans, 69.4 ng/d in Europeans, and 49.94 ng/d in the Chinese population (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%